Models of the realistic reporting of subsidies in the farm accounting - Jaroslav Sedláček; Jindřiška Kouřilová; Jiří Pšenčík (Agricultural Economics (AGRICECON), 2012)
The paper deals with subsidies in the agriculture and their sources from the perspective of their recipients. The review of literature points out the significance of subsidies for the economics of agriculture and also for the evaluation of the financial position and performance of entrepreneurial entities. The current national and supranational approaches to reporting subsidies within the farm accounting and financial statements are analyzed. The result of the analysis is an identification of distortions in the reported production power and the value of the company property, caused by the yield method which is based on the matching principle. This is also negatively reflected in the income tax base of the entities. Therefore, for a more real view of the situation in financial statements, two models suitable for reporting subsidies were proposed. These are based on the capital approach. The new approaches represent a transparent reporting of subsidies by their recipients in the form of a long-term financial source; they do not allow them to report unearned yields and, on the other hand, they do allow them to report a subsidized property at an unreduced purchase cost. Thus it is possible to compare economic data of the particular companies. This also has a positive effect on the burden of the subsidy recipients laid by income taxes.